POTENSI PASAR TRADISIONAL PRAWIROTAMAN SEBAGAI DESTINASI EXPERIENTIAL TOURISM DI YOGYAKARTA - Prabawati, Andhika Galuh; Anggia Rini, Maria Nila; Prasojo, Bintang (Jurnal Jarlit, 2025)
In recent years, global tourism trends have shifted from mass tourism toward experiential tourism and slow tourism models that emphasize deeper interaction with local culture. This transformation presents a significant opportunity to develop tourism destinations rooted in local wisdom, including traditional markets as socio-economic and cultural spaces of the community. This study aims to explore the potential of Prawirotaman Market in Yogyakarta as an experiential tourism destination through the development of a mobile walking tour application. The research adopts a qualitative descriptive approach, with data collected through participatory observation, documentation, and literature review related to experiential tourism and the digitalization of traditional markets. The results reveal that Prawirotaman Market possesses strong cultural appeal through traditional culinary products, warm social interactions, and a strategic location within an international tourist area. Although the market has undergone physical revitalization and obtained SNI 8152:2021 certification, its cultural potential remains underutilized in the digital realm. Therefore, a walking tour application model was designed that integrates interactive maps, Indonesian-language audio narration, photos, and interactive descriptions to enhance visitors’ experiences. This application not only improves navigation and information access but also serves as a medium for cultural preservation and local vendor empowerment. The study recommends collaboration between the government, local communities, and market stakeholders to implement the application and realize a sustainable smart cultural tourism concept centered on authentic visitor experiences.